Kinetics and thermodynamics analysis for ring-opening polymerization of ε-caprolactone initiated by tributyltin n-butoxide using differential scanning calorimetry - Limwanich,W. (Springer Netherlands, 2015)
© 2014 Akadémiai Kiadó, Budapest, Hungary. The bulk ring-opening polymerizations (ROP) of ε-caprolactone (ε-CL) initiated by synthesized tributyltin n-butoxide (nBu3SnOnBu) initiator were conducted at 120 °C and the molecular mass and polydispersity index of poly(ε-CL), PCL, were determined. The coordination-insertion ROP of ε-CL was confirmed by 1H-NMR. The molecular mass of PCL was successfully controlled with monomer to initiator concentration ratio. The kinetics and thermodynamics of ROP were investigated by differential scanning calorimetry (DSC) using both non-isothermal and isothermal methods. From the non-isothermal method, the activation energy (E a) of ROP of ε-CL initiated by 1.0, 1.5, and 2.0 mol% of nBu3SnOnBu was derived from the method of Kissinger (78.3, 61.1, and 59.9 kJ mol-1) and Ozawa (82.8, 66.2, and 64.9 kJ mol-1). For isothermal method, the values of E a for these three concentrations of nBu3SnOnBu were 74.2, 65.8, and 62.0 kJ mol-1, respectively. The first-order reaction model was employed to determine the apparent rate constant (k app). The degree of aggregation (m) of nBu3SnOnBu in ε-CL was also determined using isothermal method which confirmed its non-aggregated form. In addition, the activation enthalpy (ΔH ≠) and entropy (ΔS ≠) were estimated to be 70.5 kJ mol-1 and -100.3 J mol-1 K-1 by isothermal DSC. The Friedman, Kissinger-Akahira-Sunose, and Flynn-Wall-Ozawa isoconversional methods were also applied to non-isothemal DSC data to investigate the dependence of E a with monomer conversion (α). The results of all three methods were discussed and compared with isothermal and non-isothermal methods at 1.0 mol% of nBu3SnOnBu. The overall results demonstrate that DSC is a fast, convenient, and reliable method for studying the kinetics and thermodynamics of ROP of ε-CL initiated by nBu3SnOnBu.